Analisis Kualitas Pelayanan Publik Kantor Desa Cirebon Baru Kecamatan Seberang Musi Kabupaten Kepahiang - Lestari, Winda; Susanti, Neri; Noviantoro, Rinto (Journal of Management, Economic, and Accounting, 2022)
Service quality is a dynamic condition associated with products, services, people, processes, and the environment that meet or exceed expectations. Service quality must be done by the company in order to be able to survive and to win the trust of the community. This study aims to analyze the quality of public services at Cirebon Baru Village Office, Seberang Musi Sub-District, Kepahiang Regency. This type of research is descriptive of a quantitative approach that uses the Community Satisfaction Index (CSI) method Number 14 of 2017 with data results in the form of numbers. The data were obtained through interviews with the data collection instrument in the form of a questionnaire with the population or sample of the village community of Cirebon Baru, Seberang Musi Sub-District, Kepahiang Regency with a total sample of 100 respondents. The results showed that the value of the Community Satisfaction Index (CSI) for the services of the office was 3.37 with a conversion rate of 84.25, with the quality criteria “Good (B)'. The results regarding public perceptions of service quality at Cirebon Baru Village Office, Seberang Musi Sub-District, Kepahiang Regency with 9 (nine) research indicators using the community satisfaction index, it was obtained the perception that the services provided were in "Good (B)" criteria.